2017
DOI: 10.3389/fnins.2017.00649
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Ambulation by Upper Limb-Triggered HAL® in Patients with Complete Quadri/Paraplegia Due to Chronic Spinal Cord Injury

Abstract: Patients with complete paraplegia after spinal cord injury (SCI) are unable to stand or walk on their own. Standing exercise decreases the risk of decubitus ulcers, osteoporosis, and joint deformities in patients with SCI. Conventional gait training for complete paraplegia requires excessive upper limb usage for weight bearing and is difficult in cases of complete quadriplegia. The purpose of this study was to describe voluntary ambulation triggered by upper limb activity using the Hybrid Assistive Limb® (HAL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…It was also noted by Verma et al ( 2012 ) that the adult human brain is capable of reorganization after stroke and can be manipulated with movement stimuli involving lower limbs. Shimizu et al ( 2017 ) showed that recovery of neuromuscular activity is possible even in patients with chronic complete spinal cord injury with quadri/paraplegia. They used HAL to allow patients to trigger voluntary ambulation with residual muscle activations in their arms.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted by Verma et al ( 2012 ) that the adult human brain is capable of reorganization after stroke and can be manipulated with movement stimuli involving lower limbs. Shimizu et al ( 2017 ) showed that recovery of neuromuscular activity is possible even in patients with chronic complete spinal cord injury with quadri/paraplegia. They used HAL to allow patients to trigger voluntary ambulation with residual muscle activations in their arms.…”
Section: Discussionmentioning
confidence: 99%
“…A group of stroke patients treated with HAL improved their sit-to-stand movements thanks to the increment of the forward tilt angle (Kasai and Takeda, 2016 ). Additionally, spinal cord injury patients showed improvement in their spasticity (Ikumi et al, 2016 ), recovery of lower limb muscle activities (Shimizu et al, 2017 ), reduction of neuropathic pain (Cruciger et al, 2016 ) and normalization of cortical excitability and cortical plasticity (Sczesny-Kaiser et al, 2017 ). However, there is no available data about gait kinematics evaluation after HAL therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports on neural activity changes by HAL in recent literature: brain activity changes in the primary motor cortex of subacute stroke patients immediately after using HAL (81), cortical excitability changes in the primary somatosensory cortex of spinal cord injury patients after 3 months of training (16), muscle synergy changes in the lower limbs of stroke patients (50), segmental coordination changes in in the lower limbs of myelopathy patients after surgery for thoracic OPLL (11), and activation in some muscles of chronic spinal cord injury patients during and after HAL training (17).…”
Section: Discussionmentioning
confidence: 99%
“…It actuates the electric motors embedded in the hips and knees of its exoskeleton in real time, amplifying bioelectric activation of the relevant muscles which are detected using surface electrodes attached on the hip and knee muscles. Previous studies using HAL for myelopathy (10)(11)(12), spinal cord injury (13)(14)(15)(16)(17), and post-surgery rehabilitation after total knee arthroplasty (18) reported improvement of walking ability after HAL training.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation